Impact of Various pH Levels on 4-Methyl Catechol Treatment of Wood - Md. Tipu, Sultan; Md. Rezaur, Rahman; Sinin, Hamdan; Zainal Abidin, Talib; Fahmi Asyadi, Bin Md Yusof; Chang, Josephine Hui Lai (North Carolina State University, 2017)
Four types of treated wood (TW) were prepared by the impregnation of solid wood each with a solution of 4-methyl catechol at pH 8, a solution of 4-methyl catechol at pH 9, a solution of 4-methyl catechol at pH 10, and a solution of 4-methyl catechol at pH 11. These TW were characterized by Fourier transform infrared spectroscopic, X-ray diffraction (XRD), scanning electron microscopic, 3-point bending, free-free-vibration, and thermo-gravimetric analysis. FT-IR result showed that TW had more than one carbonyl absorbance band between 1745 and 1690 cm-1, while raw wood had only one carbonyl absorbance band in this regard. TW at pH levels of eight and nine showed higher crystallinity index (CIXRD) than that of raw wood. The SEM micrograph of TW at pH 8 had a smoother surface compared with other treated wood and raw wood. The modulus of elasticity (MOE), and modulus of rupture (MOR) of TW at pH 8 and pH 9 significantly increased. The raw wood exhibited a higher water uptake compared with the TW. The TGA results showed that TW were thermally less stable between 267 and 400 °C than raw wood.